Implementasi Rebranding Identity untuk Meningkatkan Brand Recognition pada Sosial Media Instagram Peachy Sun - Marissa Elsa Safiera; Tetty Herawaty; Arianis Chan; Muhammad Ali Abdurrahman (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Now there are many Micro, Small and Medium Enterprises, one of which is Peachy sun which is an MSME that produces photocards, hand banners and wall decor. The problem with this brand is the lack of brand recognition makes people not remember the brand they bought. For this problem, we rebranded several brand elements. What we have done for Peachy sun is to create a logo, have a color palette, and design a feed for Instagram peachysunid_ . Our goal is to build a brand identity which we hope can grow brand recognition and also increase sales of Peachy sun.